Effect of thermosonication treatment on blueberry juice quality: Total phenolics, flavonoids, anthocyanin, and antioxidant activity. (October 2021) - Wu, Yingmei; Xu, Longquan; Liu, Xiaoyi; Hasan, K.M. Faridul; Li, Haoxin; Zhou, Shaoqin; Zhang, Qinghai; Zhou, Yan
Abstract: To investigated the effects of thermosonication (TS) on blueberry juice quality. The raw juice (RJ), pasteurized juice (60 °C, 30 min, PJ), and TS treated juice (20 kHz, 200 W, 400 W, and 600 W at 60 °C for 15 min, TJ) were analysed for colour characteristics, total antioxidant contents, antioxidant capacity, and composition of anthocyanins. Results showed that TS treated juice had higher colour density (CD), L*, and ΔE values and lower values of chroma (C), hue angle (h), yellow index (YI). The content of total phenolics, flavonoids, and anthocyanins, were increased by 139.32%, 251.72%, and 94.12%, respectively, in TJ600 sample compared to the RJ samples. The 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radical (▪OH) scavenging capacity were increased to 65.22%, 51.13%, significantly higher than PJ sample. The content of delphinidin-3-O-glucoside (Dp-G) and cyanidin-3-O-glucoside (Cy-G), were 54.40 mg/L, 28.75 mg/L in juice. Correlation analysis indicated that the antioxidant contents play an important role in CD, and Cy-G determines the brightness or darkness of the juice. Collectively, the findings suggested that TS could be a feasible alternative to pasteurization for improving the quality and antioxidant activity of blueberry juice. Highlights: TS processing increase the content of antioxidants and the capacity of antioxidant. Colour differences were found between TS, pasteurizated, and raw blueberry juice. Colour differences in TS juice contribute to the increased TPC, TFC, and anthocyanin content. TS treatment increased delphinidin-3-O-glucoside and cyanidin-3-O-glucoside content.